A Pilot Functional MRI Study of the Effects of Prefrontal rTMS on Pain Perception. Issue 7 (3rd May 2013) - Martin, Laura; Borckardt, Jeffrey J.; Reeves, Scott T.; Frohman, Heather; Beam, Will; Nahas, Ziad; Johnson, Kevin; Younger, Jarred; Madan, Alok; Patterson, David; George, Mark
Abstract: Objective: Repetitive transcranial magnetic stimulation (rTMS) has been shown to effectively treat depression, and its potential value in pain management is emphasized by recent studies. Transcranial magnetic stimulation (TMS)‐evoked activity in the prefrontal cortex may be associated with corticolimbic inhibitory circuits capable of decreasing pain perception. The present exploratory pilot study used functional magnetic resonance imaging (fMRI) to examine the effects of left prefrontal rTMS on brain activity and pain perception. Design and Intervention: Twenty‐three healthy adults with no history of depression or chronic pain underwent an 8‐minute thermal pain protocol with fMRI before and after a single rTMS session. Participants received 15 minutes of either real (N = 12) or sham (N = 11) 10 Hz rTMS over the left prefrontal cortex (110% of resting motor threshold; 5 seconds on, 10 seconds off). Results: TMS was associated with a 13.30% decrease in pain ratings, while sham was associated with an 8.61% decrease ( P = 0.04). TMS was uniquely associated with increased activity in the posterior cingulate gyrus, precuneous, right superior frontal gyrus, right insula, and bilateral postcentral gyrus. Activity in the right superior prefrontal gyrus was negatively correlated with pain ratings ( r = −0.65, P = 0.02) in the real TMS group. Conclusions: Findings suggest that prefrontal rTMS may be capable of activating inhibitory circuits involved with pain reduction.